Effects of Low Amplitude High Velocity Thurst Manipulation as Compare to Grade III Maitland Mobilization of Thoracic Spine on Mechanical Neck Pain and Disability - Perveen, Sumaira; Zahra, Sum-Re-; Mahmood, Tahir; Haider, Rizwan; Ayub, Azhar (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To determine the effectiveness of thrust mobilization and Maitland grade III mobilization in reducing Neck pain and its disability index Methodology: This was a randomized clinical trial study. The data was collected at Mayo Hospital Lahore from December 2017 to May 2018. Total 40 patients were included in the study with primary complaint of mechanical neck pain and disability. That 40 patients were assigned to mobilization group (group A, N=20) and thrust group (group B, N=20). Both groups received 6 sessions, 3 sessions per week of respective therapy along with conservative treatment. Pre, mid and post evaluations were measured on Numeric Pain Rating Scale (NPRS) and NDI (Neck Disability Index). The data was compared with baseline data. Repeated measurement ANOVA test and independent t test ware used for the within group and between groups analysis respectively. SPSS Version 20.0 was used statistical analysis. Results: Repeated measurement ANOVA and independent t tests were used for the within group and between groups analysis respectively. No significant difference was found in any of the outcome measure between thrust and Maitland mobilization (p<0.05). Statistically significant improvement was found in both groups. Conclusions: This study concluded that both thrust and Maitland mobilization of thoracic spine were effective but thrust manipulation had superior effects in reducing neck pain and disability. Key words: Mechanical Neck Pain, Maitland mobilization, Thrust manipulation.